A ANALISIS YURIDIS FILOSOFIS TERHADAP PENTINGNYA JAMINAN KEPASTIAN HUKUM DALAM PENGEMBANGAN TRANSAKSI KEUANGAN SYARIAH - prasetyo, yogi (AL AMWAL (HUKUM EKONOMI SYARIAH), 2020)
Sharia financial institutions are considered by the community as not yet able to provide a clear guarantee of legal certainty, because there are several provisions that have not been included in positive law in this country. Some provisions of sharia financial law still do not explicitly regulate the practices of Islamic finance, such as the amount of interest that is considered lawful or unlawful, the court that has the authority to decide on sharia financial issues, practices that are almost the same or even greater with interest systems and other problems which inhibits the development of Islamic finance. People who have for many years been taught to use conventional concepts, consider safer with definite positive legal guarantees from the state. The issue of public trust should be reasonable and a positive correction in developing Islamic finance. In a community system that leads towards modernity, legal certainty is needed, so that a good legal order is needed so that the community believes in the security of transactions in Islamic financial institutions. The importance of legal certainty as a basic foundation, action plan, rules of the game, problem breakers, control and supervision in sharia financial transactions. Legal concepts are needed in the development of Islamic finance that protect the interests of society and are far from the practice of capitalism, so that in accordance with the principles in Islamic teachings as a religion that is prosperous and saves.